2019
DOI: 10.3233/jad-180964
|View full text |Cite
|
Sign up to set email alerts
|

In Brief Neuropsychological Assessment, Amnestic Mild Cognitive Impairment (MCI) Is associated with Cerebrospinal Fluid Biomarkers for Cognitive Decline in Contrast to the Prevailing NIA-AA MCI Criterion

Abstract: Background: In the care of persons with cognitive problems, it is important to use a valid mild cognitive impairment (MCI) criterion that discriminates well between normal and pathological aging. Objective: To find the brief neuropsychological screening criterion that best correlates with cerebrospinal fluid (CSF) biomarkers for cognitive decline and dementia in persons seeking help for cognitive problems. Methods: 452 consecutively recruited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 38 publications
2
8
0
Order By: Relevance
“…Demographically adjusted T-scores of CERAD word list (recall) 34 , VOSP 33 , TMT B and COWAT 35 were used for cognitive staging, defined as impaired if lower than 1.5 standard deviation below the normal population. Details on the neuropsychological battery have been provided elsewhere 36 .…”
Section: Methodsmentioning
confidence: 99%
“…Demographically adjusted T-scores of CERAD word list (recall) 34 , VOSP 33 , TMT B and COWAT 35 were used for cognitive staging, defined as impaired if lower than 1.5 standard deviation below the normal population. Details on the neuropsychological battery have been provided elsewhere 36 .…”
Section: Methodsmentioning
confidence: 99%
“…All participants were categorized using five different MCI definitions in succession. Because one aim of the current study was a longitudinal evaluation of findings from Hessen et al (2019), we This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Diagnostic and Classification Criteriamentioning
confidence: 99%
“…Memory impairment is a key feature of MCI due to AD, and meta-analytic evidence shows that impaired performance on neuropsychological memory measures in MCI predicts AD progression (Belleville et al, 2017). In a recent cross-sectional study, Hessen and colleagues (2019) compared brief neuropsychological screening criteria for MCI and their association with cerebrospinal fluid AD biomarkers. It was found that a criterion targeting amnestic MCI was more strongly associated with the NIA-AA Stage 2 (lowered CSF Aβ42 concentrations and elevated CSF tau concentrations; Sperling et al, 2011), than criteria allowing for impairment in any cognitive domain.…”
mentioning
confidence: 99%
“…More specifically, impairment in episodic memory encoding reflected in unsuccessful cued recall and susceptibility to intrusion effects has been associated with higher probability of underlying [22,23,24] even at the prodromal phase of MCI [25]. More recent studies have demonstrated that this particular cognitive profile in MCI is compatible with positive AD biomarkers [26,27,28,29,30], as well as abnormal neural connectivity [31,32,33] and cerebral perfusion patterns [34] during memory encoding tasks. Moreover, declines in memory encoding have been predicted in amyloid-positive cognitively-normal individuals [35,36,37] alongside downstream tau increases [38,39,40,41], as well as in patients with subjective cognitive complaint with positive AD biomarkers [42].…”
Section: Introductionmentioning
confidence: 99%